Gregorian Chant - Apel, Willi 1893-1988 (Bloomington, IN Indiana University Press, 1990)
Willi Apel's classic study of Gregorian chant is now in paperback. This extensive survey describes the evolutionary processes of its long history as well as its definition and terminology, the structure of the liturgy, the texts, the notation, the rhythm, the tonality, and the methods and forms of psalmody.
Originally published in 1958
Keywords: Past; Plainchant; Music history